Heart Rate Variability Triangular Index as a Predictor of Cardiovascular Mortality in Patients With Atrial Fibrillation. Issue 15 (4th August 2020) - Hämmerle, Peter; Eick, Christian; Blum, Steffen; Schlageter, Vincent; Bauer, Axel; Rizas, Konstantinos D.; Eken, Ceylan; Coslovsky, Michael; Aeschbacher, Stefanie; Krisai, Philipp; Meyre, Pascal; Vesin, Jean‐Marc; et al.
Abstract : Background: Impaired heart rate variability (HRV) is associated with increased mortality in sinus rhythm. However, HRV has not been systematically assessed in patients with atrial fibrillation (AF). We hypothesized that parameters of HRV may be predictive of cardiovascular death in patients with AF. Methods and Results: From the multicenter prospective Swiss‐AF (Swiss Atrial Fibrillation) Cohort Study, we enrolled 1922 patients who were in sinus rhythm or AF. Resting ECG recordings of 5‐minute duration were obtained at baseline. Standard parameters of HRV (HRV triangular index, SD of the normal‐to‐normal intervals, square root of the mean squared differences of successive normal‐to‐normal intervals and mean heart rate) were calculated. During follow‐up, an end point committee adjudicated each cause of death. During a mean follow‐up time of 2.6±1.0 years, 143 (7.4%) patients died; 92 deaths were attributable to cardiovascular reasons. In a Cox regression model including multiple covariates (age, sex, body mass index, smoking status, history of diabetes mellitus, history of hypertension, history of stroke/transient ischemic attack, history of myocardial infarction, antiarrhythmic drugs including β blockers, oral anticoagulation), a decreased HRV index ≤ median (14.29), but not other HRV parameters, was associated with an increase in the risk of cardiovascular death (hazard ratio, 1.7; 95% CI, 1.1–2.6; P =0.01) and all‐cause death (hazard ratio, 1.42; 95% CI, 1.02–1.98; P =0.04). Conclusions: The HRV index measured in a single 5‐minute ECG recording in a cohort of patients with AF is an independent predictor of cardiovascular mortality. HRV analysis in patients with AF might be a valuable tool for further risk stratification to guide patient management. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02105844.